Geomorphology and Geology Studies Using Digital Elevation Model (DEM) Data In the Watershed Area of Kampar Regency, Riau Province - Husnul Kausarian; Sandy Masdriyanto; Batara; Adi Suryadi; Muhammad Zainuddin Lubis (UIR PRESS, 2023)
This research was conducted in the area of ​​Kampar Regency, Riau Province .it was located at coordinates including 01° 00' 40